There are some questions you may not ask in a clinic: Providing contraception information to young people in Kenya using SMS☆. (2nd August 2013) - Vahdat, Heather L.; L'Engle, Kelly L.; Plourde, Kate F.; Magaria, Loice; Olawo, Alice
Abstract: Objective: To evaluate the acceptability, information access, and potential behavioral impact of providing contraception information via text message on mobile phones to young people in Kenya. Methods: Three methods of data collection were implemented during the 17‐month pilot period for the Mobile for Reproductive Health (m4RH) program in Kenya: automatic logging of all queries to the m4RH system; demographic and behavior change questions sent via short message service protocol (SMS) to everyone who used m4RH during the pilot period; and telephone interviews with a subset of m4RH users. Results: During the pilot period, 4817 unique users accessed m4RH in Kenya. Of these, 82% were 29 years of age and younger, and 36% were male. Condom and natural family‐planning information was accessed most frequently, although users queried all methods. One in 5 used the m4RH system to locate nearby clinics. Respondents liked the simple language and confidentiality of receiving health information via mobile phone, and reported increased contraceptive knowledge and use after using m4RH. Conclusion: Providing contraception information via mobile phone is an effective strategy for reaching young people. More research is needed to learn how to link young people to youth‐friendly services effectively.